Banned : immigration enforcement in the time of Trump - Wadhia, Shoba Sivaprasad (New York University Press, 2019)
Examines immigration enforcement and discretion during the first eighteen months of the Trump administration Within days of taking office, President Donald J. Trump published or announced changes to immigration law and policy. These changes have profoundly shaken the lives and well-being of immigrants and their families, many of whom have been here for decades, and affected the work of the attorneys and advocates who represent or are themselves part of the immigrant community. Banned examines the tool of discretion, or the choice a government has to protect, detain, or deport immigrants, and describes how the Trump administration has wielded this tool in creating and executing its immigration policy. Banned combines personal interviews, immigration law, policy analysis, and case studies to answer the following questions: (1) what does immigration enforcement and discretion look like in the time of Trump? (2) who is affected by changes to immigration enforcement and discretion?; (3) how have individuals and families affected by immigration enforcement under President Trump changed their own perceptions about the future?; and (4) how do those informed about immigration enforcement and discretion describe the current state of affairs and perceive the future? Shoba Sivaprasad Wadhia pairs the contents of these interviews with a robust analysis of immigration enforcement and discretion during the first eighteen months of the Trump administration and offers recommendations for moving forward. The story of immigration and the role immigrants play in the United States is significant. The government has the tools to treat those seeking admission, refuge, or opportunity in the United States humanely. Banned offers a passionate reminder of the responsibility we all have to protect America's identity as a nation of immigrants.